Mecanismo estrutural de regulação alostérica por potássio da enzima adenosina quinase : Structural mechanism of allosteric regulation by potassium of the enzyme adenosine kinase - Oliveira, Renata Rocha, 1980- (2018)
Orientador: Kleber Gomes Franchini